High Demand, High Commitment Work: What Residential Aged Care Staff Actually Do Minute by Minute: A Participatory Action Study - Gibson, D; Willis, E; Merrick, E; Redley, B; Bail, K (Wiley, 2022)
This article explores staff work patterns in an Australian residential aged care facility and the implications for high-quality care. Rarely available minute by minute, time and motion, and ethnographic data demonstrate that nurses and care staff engage in high degrees of multitasking and mental switching between residents. Mental switching occurs up to 18 times per hour (every 3 min); multitasking occurs on average for 37 min/h. Labor process theory is used to examine these outcomes and to explore the concepts of high demand and high commitment as core components of work intensification. These conditions of work result in high levels of cognitive burden and stress on staff in managing the multitasking and mental switching, exacerbated by lack of knowledge about residents associated with labor force casualization. These new interpretations of data in relation to mental and manual labor can contribute to understanding, and, therefore, problem solving, in the aged care sector.
Keywords: high commitment; high demand; labor process theory; mental switching; residential aged care; staff ratios; time and motion; 4203 Health Services and Systems; 42 Health Sciences; Clinical Research; Mental health; 3 Good Health and Well Being; 4204 Midwifery; 4205 Nursing; Aged; Humans; Australia; Homes for the Aged; Quality of Health Care; Anthropology, Cultural